Using Your Local Community Resources: Public Access Cablevision Channels - Bartrom, Linda (TechTrends, 2009)
Fund-raising, an earlier column, can purchase basic equipment for short-subjects and their editing, but the production studio itself is another matter; and it cannot be a oneday "field trip" if your learners are to emerge with the skills your course promises: Because YOU are the reason these stations exist.